Infections and cognitive function, depression, and frailty: a cross-sectional study in the longitudinal aging study in India (LASI) - Georgia R. Gore-Langton; Kathryn E. Mansfield; Prithvee Ravi; Arrisonia Doubatty; Suvarna Alladi; Sanjay Kinra; Charlotte Warren-Gash (BMC Public Health)
Abstract Introduction Infections may be associated with an increased risk of poor brain health and frailty among older people, but evidence from low-and-middle-income countries (LMICs) is limited. We aimed to investigate associations between nine infections and cognition, depression, and frailty in India. Methods We conducted a cross-sectional study using data from Wave 1 (2017–2019) of the Longitudinal Aging Study in India (LASI) survey of adults (≥ 45years) from 35 of India’s 36 states and union territories. Data were collected via face-to-face interviews and direct health measurements. We investigated the association between nine infections, either self-reported ever (periodontal disease) or in the two years before interview (jaundice/hepatitis, malaria, tuberculosis, typhoid, chikungunya, diarrhoea/gastroenteritis, dengue, urinary tract infection [UTI]), and measured global cognitive function, depression, and frailty. We used survey-weighted multivariable logistic regression to compare odds of impaired cognition, depression, and frailty in people with and without infections, overall and for individual infections. Results We included 64,682 respondents; median age 59 years (IQR:50–67), 53.5% female, 35% reported at least one infection. After controlling for demographic, social/environmental and lifestyle factors, and chronic health conditions, we saw evidence of associations between infection and both depression (OR: 1.28 [95%CI: 1.22–1.35]) and frailty (OR: 1.74 [95%CI: 1.65–1.84]). UTIs were associated with the highest odds of both depression (OR: 1.33 [95%CI: 1.14, 1.55) and frailty (OR: 2.94 [95%CI: 2.51, 3.44]). Reporting at least one infection was associated with reduced odds of impaired cognition (OR: 0.80 [95%CI: 0.74–0.86]). Conclusions Our results suggest infections are associated with increased depression and frailty in adults over 45 in India. Our finding of association between reported infections and better cognition, is potentially explained by preferential infection recall in those with better cognition. Longitudinal studies are needed to investigate potential causal links between infections and adverse brain health and frailty and guide interventions to improve the health of older people in India and other LMICs.